Active matrix metalloproteinase-8 and interleukin-6 detect periodontal degeneration caused by radiotherapy of head and neck cancer: a pilot study. (2nd October 2020) - Keskin, Mutlu; Lähteenmäki, Hanna; Rathnayake, Nilminie; Räisänen, Ismo T.; Tervahartiala, Taina; Pärnänen, Pirjo; Şenışık, Ahmet Murat; Karaçetin, Didem; Yentek Balkanay, Ayben; Heikkilä, Pia; Hagström, Jaana; Rautava, Jaana; et al.
ABSTRACT: Background : This cohort study investigated the role of the active matrix metalloproteinase-8 (aMMP-8) and interleukin-6 (IL-6) as oral fluid biomarkers for monitoring the periodontal degeneration occurring in head and neck cancer (HNC) patients treated by radiotherapy. Research design and methods : Eleven patients, aged 28–74, diagnosed with HNC were included in the study. Complete periodontal and oral examinations were performed pre-radiotherapy and 1 month after radiotherapy. Mouthrinse samples (pre-radiotherapy, after 6 weeks of radiotherapy and 1 month after radiotherapy) were assayed by aMMP-8 point-of-care-kit (PerioSafe®/ORALyzer®) for aMMP-8 and ELISA for IL-6. Results : HNC radiotherapy had a deteriorating impact on the periodontium and a significant impact on periodontal biomarkers aMMP-8 and IL-6 and increased their levels in mouthrinse. Clinical-attachment-loss (CAL) (site of greatest loss: mean = 1.7 mm, range = 1–3 mm) corresponding to rapid progression of periodontitis. There was a positive repeated measures correlation (rmcorr = 0.667) between the aMMP-8 and IL-6 levels. Conclusions : Elevated aMMP-8 levels were observed 1 month after radiotherapy among some HNC patients suggesting a prolonged increased susceptibility to further periodontal tissue destruction. Currently available aMMP-8 point-of-care testing could be useful to monitor and assess quantitatively online and real-time the risk of deterioration of periodontal health during HNC radiotherapy.